Continuous Deposition of Organo‐Chlorinated Thin Films by Atmospheric Pressure Dielectric Barrier Discharge in a Wire‐Cylinder Configuration. Issue 11 (18th October 2014) - Vandenabeele, Cédric; Maurau, Rémy; Bulou, Simon; Siffer, Frederic; Gérard, Mathieu; Belmonte, Thierry; Choquet, Patrick
<x xml:space="preserve">Abstract</x> On‐line atmospheric pressure plasma treatment of cylindrical substrates is of great interest in tire industry in view of developing a cheaper and cleaner process than electrolytic plating ones that are applied on metallic tire reinforcing materials. Here we assess the feasibility of such a continuous treatment by depositing organo‐chlorinated thin films from dichloromethane on zinc‐plated steel wires crossing a tubular dielectric barrier discharge. We show that working conditions highly influence layers growth and have to be carefully adjusted for obtaining homogeneous and defect‐free coatings. Thin films chemistry is strongly dependent on the energy injected in the discharge. Layers become more inorganic when power increases, resembling carbon black or graphite and no longer hydrocarbon.<inline-graphic xlink:href="ark:/27927/pgh2ckn3hsm" content-type="ppap201400098-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />